Strand 2: Implementing Telelearning: Decision Support for Instructors, The TeleTOP project - Fisser, Petra; de Boer, Wim (Proceedings of the International Conference on Networked Learning, 1998)
One of the telelearning initiatives at the University of Twente in the Netherlands is the TeleTOP project at the Faculty of Educational Science and Technology. The overall goal of the project is to stimulate the innovative and appropriate use of telematics for learning purposes within the faculty in order to make the educational delivery more efficient, more enriched, and more flexible. In practice over 30 existing courses will be modified towards WWW-based courses. A decision support tool is developed and used during individual meetings between instructors and the technical team, thereby involving the staff of the faculty. The decision support tool makes it easier for instructors to make decisions with regard to the components that they need in their WWW-based learning environment. In practice, the instructors and the team use the decision support tool and decide what can and will be adapted in the existing courses. The next step is prototyping a first concept of the adapted course. This adapted course will show the possibilities of a WWW-based course and is presented to the instructors. The second prototype will comprise actual course materials and is subject to discussion. This process will go on until the final version of the new adapted course is finished.